Cross-Sectional Survey of Views on COVID-19 and Its Vaccines Among Pregnant Women. Issue 2 (9th April 2023) - Li, Yan Yu; Lok, Wing Yi; Poon, Liona C.; Kong, Choi Wah; To, William W.K.
Abstract: Objective: The objective of this study is to evaluate the acceptance of pregnant women with regards to coronavirus disease 2019 (COVID-19) vaccination during pregnancy and to identify any significant changes in their anxiety and knowledge on COVID-19 compared to our previous study. Methods: This cross-sectional survey was performed in the antenatal clinics of United Christian Hospital and Tseung Kwan O Hospital of Hong Kong, China. Questionnaires were distributed to pregnant women for self-completion when attending follow-up from August to October 2021. Apart from basic demographic data, the questionnaire comprised of questions including knowledge on COVID-19 and its vaccines in pregnancy as well as attitudes and behaviors of pregnant women and their partners toward COVID-19. Continuous variables were analyzed by Student's test and Levene's test was used to confirm normal distribution and homogeneity of variance for continuous variables, whereas categorical variables were analyzed by the Chi-squared test or Fisher's exact test as appropriate. A P value of <0.05 was considered to be statistically significant. Results: A total of 816 completed questionnaires were included for analysis. Pregnant women were less worried about COVID-19 in the current survey as compared to the last survey (393/816, 48.2% vs . 518/623, 83.1%, P ?<?0.001). Fewer pregnant women believed that pregnancy were more susceptible to contract SARS-CoV-2 as compared to the last survey (265/816, 32.5% vs . 261/623, 41.9%, P ?<?0.001). They have significant knowledge gap and concerns about COVID-19 vaccines. Nearly half of the participants believed that pregnant women cannot have COVID-19 vaccination (402/816, 49.3%) and it is unsafe to fetus (365/816, 44.7%). Around a third of women perceived that they were more prone to the side effects and complications of COVID-19 vaccines than the general population (312/816, 38.2%) and did not recognize that maternal COVID-19 vaccination could effect transferral of antibodies to the fetus to promote postnatal passive immunity (295/816, 36.2%). Most of them had not been vaccinated (715/816, 87.6%) and only (12/715) 1.7% of them would consider vaccination during pregnancy. Conclusion: Despite the local and international recommendations for pregnant women to be vaccinated, the uptake of COVID-19 vaccines during pregnancy remained extremely low. Efforts should be made to effectively provide information about the safety and benefits of COVID-19 vaccines during pregnancy. There is an urgent need to booster vaccination rates in pregnant women to avoid excessive adverse pregnancy outcomes related to COVID-19.